Aprendendo a falar e a escrever com as mãos: o professor alfabetizador diante do desafio de alfabetizar a criança surda - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
This research, which is articulated to the Studies of Education and Language carried out by the Group of Study and Intervention in Reading, Writing,and Literature in school settings - Lelit, focuses on the theme: literacy teaching of deaf children. The problem of research is writing acquisition of deaf people, specially children, in initial Reading instruction, and the pedagogical strategies to be proposed and developed with the aim at teaching them how to read. The objective of this study is to verify how the cycle of literacy teachers of deaf children percieve and interact with what has been academically and politically produced in the referred area of scientific knowledge. To achieve the investigation objective, we postulate, based upon literature references, a set of nuclear questions that may permit both the identification of the propositions and the formulations, and also a comprehension of how the literacy teachers, who teach deaf children, have of this process, In that way, it is possible to examine the ap proximation and tensions between these two poles – theory and practice – in the current pro cess of literacy of deaf children in regular education. This dissertation is divided into two parts: one conceptual and another empirical. In the conceptual part the conceptions and the propositions are recovered through the previous investigation questions. In the empirical data collection, a guided intervew, with the same questions asked in the literature reference was used. The analysis was made based upon the narratives of the speech of the literacy teachers, inspired on the work of Bernad Lahire (2004), aiming at a consistent and systematic presenta tion, to make clear what the teachers will report. Three questions, which are the main ele ments involved in the reseached topic, emerged from the comparative analysis: 1st – the con cepts and the strategies of teaching and learning of deaf children; 2nd – the relevance of Bra zilian Sign language (LIBRAS) for the literacy teaching of deaf children; and 3rd – the partici pation of school members in the literacy teaching process of deaf children. The results suggest that some of the perceptions of the literacy teachers are closely related to the theoretical as pects of researches in the same field of investigation, such as bilingual teaching, valorization of visual aids in teaching practices, and the use of LIBRAS for the acquisition of seond lan guage, other results show the distance of what is percieved by the teachers in relation to what is proposed as reference in the field, such as the idea of what it is to teach literacy and how social inclusion processes occur.
Keywords: Educação; Educação especial; Crianças surdas; Surdez-concepções; Alfabetização; CNPQ::EDUCAÇÃO::EDUCAÇÃO ESPECIAL; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS.; EDUCAÇÃO. EDUCAÇÃO ESPECIAL